Ethanol Extract of Pomegranate Peel (Punica Granatum) in Inhibiting HeLa Cell Proliferation - Latifah Rahman Nurfazriah; Diah Dhianawaty; Andri Rezano; Ludovicus Edwinanto (PT.Mantaya Idea Batara, 2024)
Cervical cancer is one of the causes of death in women in Indonesia. Many studies have been conducted to determine the anti-cancer effects of natural ingredients. Pomegranate peel contains ellagic acid which has anti-cancer effects. In this study, the anti-cancer activity of pomegranate peel was examined against HeLa cell lines. Pomegranate peel was obtained from Malang, East Java, extracted using 70% ethanol. Cell viability and IC50 values were examined using the MTT test after incubation for 24, 48, and 72 hours. The percentage of living cells was calculated using a hemocytometer using Trypan Blue staining. DNA fragmentation was examined using electrophoresis as a marker of apoptosis activation. The IC50 value in pomegranate peel extract was at a concentration of 450 µg/ml. The results of the percentage of viability cells using hemocytomete at an IC50 concentration of 52%. Smears in DNA fragmentation examination were seen in samples incubated for 24 hours, indicating apoptosis activation. Pomegranate peel extract has anticancer activity against HeLa cell lines, with a mechanism involving apoptosis. This potential indicates that pomegranate peel extract can be further developed as a natural anticancer agent